Lung dendritic cells facilitate extrapulmonary bacterial dissemination during pneumococcal pneumonia - Rosendahl, Alva; Bergmann, Simone; Hammerschmidt, Sven; Goldmann, Oliver; Medina, Eva (Frontiers in Cellular and Infection Microbiology, 2013)
Streptococcus pneumoniae is a leading cause of bacterial pneumonia worldwide. Given the critical role of dendritic cells (DCs) in regulating and modulating the immune response to pathogens, we investigated here the role of DCs in S. pneumoniae lung infections. Using a well-established transgenic mouse line which allows the conditional transient depletion of DCs, we showed that ablation of DCs resulted in enhanced resistance to intranasal challenge with S. pneumoniae. DC-depleted mice exhibited delayed bacterial systemic dissemination, significantly reduced bacterial loads in the infected organs and lower levels of serum inflammatory mediators than non-depleted animals. The increased resistance of DC-depleted mice to S. pneumoniae was associated with a better capacity to restrict pneumococci extrapulmonary dissemination. Furthermore, we demonstrated that S. pneumoniae disseminated from the lungs into the regional lymph nodes in a cell-independent manner and that this direct way of dissemination was much more efficient in the presence of DCs. We also provide evidence that S. pneumoniae induces expression and activation of matrix metalloproteinase-9 (MMP-9) in cultured bone marrow-derived DCs. MMP-9 is a protease involved in the breakdown of extracellular matrix proteins and is critical for DC trafficking across extracellular matrix and basement membranes during the migration from the periphery to the lymph nodes. MMP-9 was also significantly up-regulated in the lungs of mice after intranasal infection with S. pneumoniae. Notably, the expression levels of MMP-9 in the infected lungs were significantly decreased after depletion of DCs suggesting the involvement of DCs in MMP-9 production during pneumococcal pneumonia. Thus, we propose that S. pneumoniae can exploit the DC-derived proteolysis to open tissue barriers thereby facilitating its own dissemination from the local site of infection.